2022
DOI: 10.3390/ani12141844
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intra-Articular Autologous Adipose Micrograft for the Treatment of Osteoarthritis in Dogs: A Prospective, Randomized, Controlled Study

Abstract: The purpose of this study was to estimate the safety, feasibility, and efficacy of the intra-articular treatment of autologous microfragmented adipose tissue in dogs with spontaneous osteoarthritis (OA) in comparison with hyaluronic acid (HA), the standard intra-articular treatment. Specifically, it clinically evaluated pain and lameness, the radiographic progression of osteoarthritis, and synovial fluid inflammation. This was a prospective, single-center, parallel-group, randomized, controlled, in vivo clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 109 publications
(138 reference statements)
0
6
0
1
Order By: Relevance
“…Anesthesia was maintained with 1.2% isoflurane in oxygen for the radiographic evaluation. The radiographic examination was performed, and orthogonal projections of the affected joint were obtained from each patient to blindly assess the OA according to the modified Kellgren–Lawrence scale (Table 4 ): score 0 = normal (grade 0); score 1–3 = mild OA (grade 1); score 4–6 = moderate OA (grade 2); score 7–9 = severe OA (grade 3); score > 10 = extremely severe/deforming OA (grade 4) 13 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anesthesia was maintained with 1.2% isoflurane in oxygen for the radiographic evaluation. The radiographic examination was performed, and orthogonal projections of the affected joint were obtained from each patient to blindly assess the OA according to the modified Kellgren–Lawrence scale (Table 4 ): score 0 = normal (grade 0); score 1–3 = mild OA (grade 1); score 4–6 = moderate OA (grade 2); score 7–9 = severe OA (grade 3); score > 10 = extremely severe/deforming OA (grade 4) 13 .…”
Section: Methodsmentioning
confidence: 99%
“…Currently, OA can be detected in the later stages of the disease because it is diagnosed predominantly through clinical examination and diagnostic imaging 12 , and there is no definitive treatment that can stop the progression and cure the disease 11 . For this reason, the scientific literature has increased its interest in researching novel therapies 13 , 14 and alternative detection methods for early diagnosis and monitoring of disease activity and progression 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Intra-articular injection of human umbilical cord matrix-derived MSCs (umMSCs) increased regenerated cartilage thickness and improved articular surface appearance on magnetic resonance imaging (MRI) ( Zhang B. Y. et al, 2018 ). Adipose tissue-derived MSCs (aMSCs) and umMSCs injections also trended towards suppressed blood/synovial inflammatory markers, including interleukin-6 and tumor necrosis factor-alpha ( Botto et al, 2022 ). Moreover, intra-articular knee injection of 10 million allogenic bone marrow-derived MSCs (bMSCs) and hyaluronic acid (HA) encouraged cartilaginous tissue formation in chondral defects on gross and histologic analysis, compared to HA or saline alone ( Li et al, 2018 ).…”
Section: Large Animal Models For Msc-based Articular Cartilage Regene...mentioning
confidence: 99%
“…In human medicine, studies have shown the potentiality of MFAT administration in plastic surgery, wound and fistula healing, and in management of degenerative chronic diseases (osteoarthrosis and diabetes) [ 48 , 49 , 50 , 51 , 52 ]. On the other hand, the scientific literature concerning the use of MFAT in veterinary medicine is very limited [ 53 , 54 , 55 , 56 ]. To our knowledge, there have been no previous studies evaluating the effect of MFAT on bone healing in either human or veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%